Incorporation of glass fibre fabrics waste into geopolymer matrices: An eco-friendly solution for off-cuts coming from wind turbine blade production. (30th October 2018) - Novais, Rui M.; Carvalheiras, J.; Capela, M.N.; Seabra, M.P.; Pullar, R.C.; Labrincha, J.A.
Graphical abstract: Highlights: Glass fibre fabrics off-cuts coming from wind turbine blade production were reused. This waste was used for the first time to produce fibre reinforced geopolymers. The fabrics significantly increase geopolymers' flexural strength (up to 144%). This study provides a sustainable solution for glass fibre off-cuts. The fabrics reuse enhances the global sustainability of wind energy production. Abstract: In this investigation, an innovative and sustainable solution for glass fibre off-cuts is proposed. For the first time, glass fibre fabrics (non-woven mat) produced during wind turbine blade manufacture were used to produce reinforced inorganic polymer composites. The influence of fabric amount on the composites' microstructure, water absorption, strength and apparent density was investigated. Results show that the fabrics exhibited an impressive flexural strength gain (up to 144%) at the 28th day, when compared to the non-reinforced geopolymer, while simultaneously increasing the composites' ductility. This feature may extend the application range of such geopolymers. Moreover, the fabric prevents the complete collapse of the composites upon failure, while the matrix alone fails catastrophically under load.